Improving spatial resolution of soil fugitive dust emission inventory using RS-GIS technology: An application case in Tianjin, China. (October 2018) - Li, Tingkun; Bi, Xiaohui; Dai, Qili; Liu, Baoshuang; Han, Yan; You, Haoyan; Wang, Lu; Zhang, Jiaying; Cheng, Yuan; Zhang, Yufen; Wu, Jianhui; Tian, Yingze; et al.
Abstract: Soil fugitive dust (SFD) contributes significantly to ambient particulate matter (PM) in Northern China. In this study, an improved method is developed to establish a high spatial resolution SFD emission inventory through the use of remote sensing (RS) -geographical information system (GIS) technology based on the wind erosion equation (WEQ) . The purpose of the application of RS is to obtain vegetation coverage data, which can be achieved through the supervised classification of land use and retrieval of vegetation coverage. Vegetation coverage was then converted to vegetative cover factor by adopting the approach given in this study. Given that the excellent spatial data analysis and the calculation function of the GIS, the high-spatial-resolution vegetative cover factor, soil texture, control efficiency, and other parameters could be multilayer nested and calculated. The SFD emission inventory is eventually obtained, with the highest spatial resolution of 30 m. As an application case, the SFD emission inventory of Tianjin city in 2013 was established with an activity level of 6383 sq. km. bare land, and 27.14 kt, 14.39 kt, 6.240 kt emitted TSP, PM10, PM2.5, respectively. Moreover, the Calpuff model was used to simulate the contributions of SFD to ambient springtime PM10 and compare the predicted PM10 to observation data to explore the feasibility of this method. This study could be a reference for the establishment of a high spatial resolution SFD emission inventory in dust dominated regions, providing information that will meet the requirement of air quality models and support the efforts of government to reduce particulate matter pollution. Graphical abstract: Image 1 Highlights: An improved method was developed to establish bottom-up soil fugitive dust emission inventory. RS-GIS technologies were applied as indispensable tools. Landsat 8 satellite data was used for interpreting vegetation coverage. High spatial resolution dust emission inventory of Tianjin was established.